Pneumoparotid: Practical impact of Surgeon performed Ultrasound in an effective Diagnostic Approach - Goncalves, Miguel; Sievert, Matti; Mantsopoulos, Konstantinos; Schapher, Mirco; Müller, Sarina Katrin; Iro, Heinrich; Koch, Michael (Oral Diseases, 2022)
Objectives: Pneumoparotid is characterized by air inclusions in the parotid duct system. Use of ultrasound has proved valuable for evaluating air inclusions in various parts of the body; the diagnostics of this condition has not been systematically analyzed, however. The aim of this study was to evaluate the value of ultrasound in the detection of air inclusions along the parotid duct system and its closer characterization. Methods: Retrospective analysis was carried out of patients diagnosed with pneumoparotid between 2005 and 2020 in a salivary gland center. Ultrasound was performed in all cases, and features of air inclusions were described. Reference standard was the clinical demonstration of foamy saliva after gland massage and/or sialendoscopic evidence of intraductal air inclusions. Results: Twenty-one patients were identified (48.8 ± 3.8 years). Two were associated with wind instruments; seven were iatrogenic, following treatment for duct stenosis; one after radiotherapy; four with known bruxism and seven were idiopathic and without associated conditions. On ultrasound examination, pneumoparotid was characterized by three phenomena: flattened, mobile hyperechoic reflexes, dirty shadows with reverberation or “sunbeam effect,” and shifting shadows during gland massage. Conclusions: Ultrasound was useful for characterizing pneumoparotid in a fast and practical way and could serve as imaging tool of first choice.
CRIS-Team Scopus Importer:2022-07-15
Keywords: diagnostics; parotid gland; pneumoparotid; ultrasound